Voice Linguists on the Record: An Introspective Investigation of Foreign-Language Transcribers at Work - Rudd, Denise; Fraser, Janet (Meta, 2000)
AbstractEven a broad definition of interpreting and translation — the interlingual transfer of the spoken and the written word respectively — would normally exclude any linguistic activity involving the recording and transcription of speech. However, an apparently unconnected group of language professionals, including foreign-language transcribers or' voice linguists,' UN précis-writers, market research analysts, and film sub-titlers, is engaged in the transcription of speech coupled with its transfer into a second language.The study described in this paper centres on the work of voice linguists and uses introspective accounts to investigate the processes involved and to identify the skill-set they use. It concludes that the work of such voice linguists involves a unique combination of inferencing and puzzle solving to resolve the difficulties of aural comprehension and a distinct, but essentially translation-based, approach to the subsequent written expression.